The impact of stress, recovery and coping on burnout symptoms of young elite table-tennis players: A prospective multilevel study - Martinent, Guillaume; Cece, Valérian; Guillet-Descas, Emma (Frontiers in Psychology, 2022)
Objective. The aim of the present study was to explore the role of stress, recovery, and coping on table tennis athlete burnout symptoms in considering both the roles of individual and contextual (training center) factors. Methods: Youth elite table-tennis players (50 girls, 109 boys; Mage=14.07, SD=2.13) involved in 15 intensive training centers completed self-report questionnaires and socio-demographic data. Results: When time 1 (T1) levels 1 (individual) and 2 (training group, contextual factor) stress, recovery, and coping were simultaneously entered as predictors of each of the three burnout symptoms (physical and emotional exhaustion, sport devaluation, reduced accomplishment) at T2 (controlling for levels 1 and 2 burnout at T1), the results of multilevel analyses revealed that: (a) T1 level 1 recovery significantly negatively predicted T2 reduced accomplishment (β=-.23, p=.03); (b) T1 level 2 disengagement-oriented coping significantly negatively predicted T2 reduced accomplishment (β=-.71, p=.03); and (c) T1 level 2 task-oriented coping marginally significantly positively predicted T2 physical and emotional exhaustion (β=.99, p=.06). Conclusion: Results of the present study provided evidence for the usefulness to disentangle the variances attributable to the individual (level 1) and contextual (level 2; training group) levels of the predictors (recovery, stress and coping) of athlete burnout. Moreover, rather than examining the antecedent role of stress on athlete burnout, it could be particularly fruitful to explore theoretical constructs able to annihilate the maladaptive effects of chronic stress such as coping and recovery.